Fracking - From, Jonte (2017)
This review aims to summarize the current knowledge about the environmental impacts and risks about fracking and to answer the question if, on the whole, it is worth it? Peer-reviewed articles mainly from the database “Web of Science” were used. The world’s fossil fuels are rapidly running out and new sources of energy are required. Vast resources of natural gas trapped within tight shale formations have been found and can be acquired by using a combination of horizontal drilling and hydraulic fracturing (fracking). This unconventional gas development is most broadly used in the USA, where the industry has expanded very quickly and left much of the research based science lagging behind. The process is not without its risks, however, and poses a threat to both the environment and public health in the form of contamination through air, soil, surface and groundwater. Lacking regulations, leakages, large numbers of well sites and low transparency have given the industry a low public acceptance. Even though economical wealth is often sure to be gained, many countries in Europe have temporarily banned the practices, awaiting further research before making any final conclusions. With the risk that near-zero emission systems may be delayed due to investing in further fossil fuels it may not be such a step towards clean energy as was first thought. With the evidence at hand, it is highly uncertain that the short-term gains are worth the long-term risks.